PENGARUH FREKUENSI DAN DURASI MENYUSUI TERHADAP KEJADIAN IKTERUS PADA BAYI BARU LAHIR: EVIDENCE BASED CASE REPORT (Jurnal Kesehatan Siliwangi, 2022)
Jaundice is the number 2 cause of death in newborns in Indonesia. Jaundice is a common problem in infants and if not treated immediately can lead to an emergency. Based on data from the Ministry of Health Republic of Indonesia in 2015, 9% of infant mortality was caused by jaundice. One way to reduce the amount of jaundice in newborns is to breastfeed as soon as possible after the baby is born because breast milk can increase intestinal motility and introduce bacteria to the intestine. If the baby isn’t breastfeeding, or breastfeeding less often, the baby may become dehydrated, buildup bilirubin and eventually develop jaundice.This evidence-based case report aimed to analyze the effect of frequency and duration of breastfeeding on the incidence of jaundice in newborns. Articles were searched through PubMed and Cochrane. One prospective cohort article was obtained, analyzed by Chi-square test, T-test, and Fisher fit test by Sukwadee Ketsuwan, Nongyao Baiya, et al. was suitable to the small research to be done. After critical review, the study by Sukwadee and Nongyao, et al. is valid, important, and applicable to patients. There is a statistically significant difference in the parameters of breastfeeding with jaundice in newborns.. Key words: effect, frequency, duration, breastfeeding, jaundice, newborn